ВИСМУТ-СУРМА ТЕЛЛУРИД ЮПҚА ПАРДАЛАРНИНГ ЭЛЕКТРОФИЗИК ХОCCАЛАРИГА ТЕХНОЛОГИК ЖАРАЁННИНГ ТАЪСИРИ (Scientific journal of the Fergana State University, 2023)
In this article dependence electrophysical  characters of P-type semiconductor fine films on base of the admixtures Bi, Sb and Te from the temperature substrate is explored.